Penerapan Teknologi Augmented Reality Untuk Edukasi Hewan Purbakala Dengan Metode Marker Tracking Pada Snapchat - Yoga Sahria; Putu Sudira; Ike Yunia Pasa (Progresif: Jurnal Ilmiah Komputer, 2023)
Ancient animals are animals that existed in the past and are now extinct, the remains of which are bones called fossils. The introduction of ancient animals so far still uses books that seem boring in the form of pictures, two dimensions, paintings and other props. This is felt to be less effective, it seems not interactive, it only looks at one side, so it needs education that is more interesting, fun and looks real. This research aims to introduce interactive, interesting, innovative ancient animals that are expected to be able to provide an easy experience in recognizing ancient animals that lived in prehistoric times into more real-time characters. The methodology in its development uses the Multimedia Development Life Cycle (MDLC) the steps consist of concept, design, material collecting, assembly, testing, distribution. The results of this study succeeded in displaying 3-dimensional objects in the form of ancient animals as interactive, interesting, innovative, practical, valid, effective ancient animal recognition media. The test results on several versions of Android in the form of image objects have a high degree of accuracy.Keywords: Augmented Reality Technology; Ancient Animals; Marker Based Tracking AbstrakHewan purbakala merupakan hewan yang sudah ada masa lampau dan sekarang sudah punah peninggalannya berupa tulang yang disebut fosil. Pengenalan hewan purbakala selama ini masih menggunakan buku terkesan membosankan berbentuk gambar, dua dimensi, lukisan dan alat peraga lain, Hal ini dirasa kurang efektif terkesan tidak interaktif hanya dilihat pada suatu sisi saja, sehingga perlu edukasi yang lebih menarik, menyenangkan, dan terlihat seperti nyata. Penelitian ini bertujuan untuk mengenalkan hewan purba yang interaktif, menarik, inovatif diharapkan mampu memberikan pengalaman kemudahan dalam mengenali hewan purba yang hidup pada zaman prasejarah kedalam karakter yang real time lebih nyata. Metodologi dalam pengembangannya menggunakan Multimedia Development Life Cycle (MDLC) langkah-langkahnya terdiri dari concept, design, material collecting, assembly, testing, distribution. Hasil penelitian ini berhasil menampilkan objek 3 dimensi berupa hewan purba sebagai media pengenalan hewan purba interaktif, menarik, inovatif, efektif dan praktis. Hasil pengujian pada beberapa versi android berupa objek gambar memiliki tingkat keakuratan yang tinggi.Kata Kunci: Teknologi Augmented Reality; Hewan Purba; Marker Based Tracking